2012
DOI: 10.1007/s10508-012-9905-y
|View full text |Cite
|
Sign up to set email alerts
|

Provoked Vestibulodynia: Mediators of the Associations Between Partner Responses, Pain, and Sexual Satisfaction

Abstract: Provoked vestibulodynia (PVD) is a chronic, recurrent vulvo-vaginal pain condition affecting 12% of the general population, and is associated with sexual dysfunction, psychological distress, and reduced quality of life. There is growing interest in the role of interpersonal variables in PVD, which have been widely neglected. In a sample of 175 couples, the present study examined the mediating roles of partner and participant catastrophizing and self-efficacy in the association between solicitous partner respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 69 publications
5
49
1
Order By: Relevance
“…Furthermore, the associations were mediated by greater patient and partner pain catastrophizing and self-efficacy [39,40]. In fact, partner pain catastrophizing and selfefficacy directly predicted patient pain, suggesting that the partner's view of the pain may modulate patient symptomatology [41].…”
Section: B Psychosocial Precursors/maintenance Factorsmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, the associations were mediated by greater patient and partner pain catastrophizing and self-efficacy [39,40]. In fact, partner pain catastrophizing and selfefficacy directly predicted patient pain, suggesting that the partner's view of the pain may modulate patient symptomatology [41].…”
Section: B Psychosocial Precursors/maintenance Factorsmentioning
confidence: 94%
“…demonstrations of anger, were significantly associated with higher levels of pain during intercourse, suggesting that partner responses, both positive and negative, may play a role in the experience of vulvovaginal pain [38]. Results from a larger cross-sectional study of 191 couples indicated that higher solicitous partner responses -assessed from the perspective of both the 8 woman and partner -were associated with higher levels of women's pain intensity.Furthermore, the associations were mediated by greater patient and partner pain catastrophizing and self-efficacy [39,40]. In fact, partner pain catastrophizing and selfefficacy directly predicted patient pain, suggesting that the partner's view of the pain may modulate patient symptomatology [41].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In the context of PVD, an example of a solicitous response is when a partner suggests that the couple stop engaging in sexual activity; a negative response is when a partner expresses anger or disappointment. Both are associated with worse pain outcomes in cross-sectional and daily diary studies of musculoskeletal pain and PVD 4,5,28,30,32,33,37,39 . Negative partner responding, more so than solicitous responding, has been shown to be related to patient depressive symptoms, which may be due to the perceived supportiveness of solicitous responses 4,30,37 Less is known about why partners respond in specific ways, but based on a cognitive behavioral framework, partner cognition regarding pain may influence their subsequent behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This could indicate changes in partners' ability or desire to respond in positive ways as time goes on, suggesting that positive behavioral responding may take more self-regulation. One study showed that partner catastrophizing and self-efficacy partially mediated the association between higher partner solicitous responses and higher pain during intercourse in women with PVD, although only pain catastrophizing was a unique mediator 3,32 .…”
Section: Introductionmentioning
confidence: 99%